Regional now- and forecasting for data reported with delay: toward surveillance of COVID-19 infections - Giacomo De Nicola; Marc Schneble; Göran Kauermann; Ursula Berger (AStA Advances in Statistical Analysis, 2022)
Governments around the world continue to act to contain and mitigate the spread of COVID-19. The rapidly evolving situation compels officials and executives to continuously adapt policies and social distancing measures depending on the current state of the spread of the disease. In this context, it is crucial for policymakers to have a firm grasp on what the current state of the pandemic is, and to envision how the number of infections is going to evolve over the next days. However, as in many other situations involving compulsory registration of sensitive data, cases are reported with delay to a central register, with this delay deferring an up-to-date view of the state of things. We provide a stable tool for monitoring current infection levels as well as predicting infection numbers in the immediate future at the regional level. We accomplish this through nowcasting of cases that have not yet been reported as well as through predictions of future infections. We apply our model to German data, for which our focus lies in predicting and explain infectious behavior by district.
Keywords: 510; Nowcasting; Forecasting; COVID-19; Generalized regression models; Delayed reporting; Disease mapping